2021
DOI: 10.1016/j.gore.2021.100853
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical Index of Stable febrile neutropenia risk stratification system for management of febrile neutropenia in gynecologic oncology patients

Abstract: Highlights The CISNE score is able to accurately identify a cohort of gynecologic oncology patients with low-risk febrile neutropenia. The CISNE performs similarly to the MASCC score when low-risk and intermediate-risk patients are grouped together. Lowering the CISNE threshold for low-risk febrile neutropenia may be a safer method of caring for gynecologic patients. Using the MASCC followed by CISNE with the lower threshold yielded the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…20 Previous exposure to radiotherapy, identified in 24.13% of FN events, is consistent with the findings of Monuszko et al who demonstrated that 24% of patients who developed FN had received radiation along with chemotherapy. 6 In a study conducted in the United States, the number of hospitalizations for cancer-related neutropenia was 5.2%, and the length of hospitalization was 0 to 7 days. 21 In the present study, approximately 55% of the patients were hospitalized for 5 to 9 days, and those who remained for more than 20 days (6.89%) had associated comorbidities and died.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20 Previous exposure to radiotherapy, identified in 24.13% of FN events, is consistent with the findings of Monuszko et al who demonstrated that 24% of patients who developed FN had received radiation along with chemotherapy. 6 In a study conducted in the United States, the number of hospitalizations for cancer-related neutropenia was 5.2%, and the length of hospitalization was 0 to 7 days. 21 In the present study, approximately 55% of the patients were hospitalized for 5 to 9 days, and those who remained for more than 20 days (6.89%) had associated comorbidities and died.…”
Section: Discussionmentioning
confidence: 99%
“…Previous exposure to radiotherapy, identified in 24.13% of FN events, is consistent with the findings of Monuszko et al who demonstrated that 24% of patients who developed FN had received radiation along with chemotherapy. 6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations